2020
DOI: 10.1371/journal.pbio.3001023
|View full text |Cite
|
Sign up to set email alerts
|

Prior expectations evoke stimulus-specific activity in the deep layers of the primary visual cortex

Abstract: The way we perceive the world is strongly influenced by our expectations. In line with this, much recent research has revealed that prior expectations strongly modulate sensory processing. However, the neural circuitry through which the brain integrates external sensory inputs with internal expectation signals remains unknown. In order to understand the computational architecture of the cortex, we need to investigate the way these signals flow through the cortical layers. This is crucial because the different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 93 publications
(156 reference statements)
10
44
0
Order By: Relevance
“…Importantly, for the first time we resolved the depth-profile of such sequence-level information. In accordance with predictive coding and the notion that predictive top-down information should be strongest in deeper layers (Kok et al 2016; de Lange et al 2018; Aitken et al 2020), we found the significant difference with ISC intact > ISC scrambled to be observed in the deeper half of PFt, peaking at a depth that aligns with layer V in postmortem histological examinations of the brains of other individual(Caspers et al 2006). In line with anatomical tracing studies in monkeys, suggesting that feedback connections from BA44 to PFt should terminate in layer III in addition to layers V/VI, this increased ISC was significant also at depth compatible with the location of layer III.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Importantly, for the first time we resolved the depth-profile of such sequence-level information. In accordance with predictive coding and the notion that predictive top-down information should be strongest in deeper layers (Kok et al 2016; de Lange et al 2018; Aitken et al 2020), we found the significant difference with ISC intact > ISC scrambled to be observed in the deeper half of PFt, peaking at a depth that aligns with layer V in postmortem histological examinations of the brains of other individual(Caspers et al 2006). In line with anatomical tracing studies in monkeys, suggesting that feedback connections from BA44 to PFt should terminate in layer III in addition to layers V/VI, this increased ISC was significant also at depth compatible with the location of layer III.…”
Section: Discussionsupporting
confidence: 86%
“…Because this increased ISFC is calculated across different subjects, it indicates that it is signal relating to the intactness of the sequence in the stimuli that synchronizes across BA44 and PFt (Simony et al 2016; Nastase et al 2019). The depth of this channel of increased ISFC dovetails remarkably well with recent observations that predictive processes in other domains of visual processing are accompanied by an increased recruitment of the deeper layers of the cortical visual system (Kok et al 2016; de Lange et al 2018; Aitken et al 2020), and with anatomical consideration that the dominant origin of feedback originates from deep layers in higher cortical region(Shipp 2007).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The behavioural signature of statistical distractor-location learning has been well documented recently: RT interference is reduced for distractors occurring at frequent versus rare locations, and this is associated with reduced capture of the first saccade by distractors at frequent locations (Di Caro et al 2019;Wang et al 2019a;Sauter et al 2020). Together with an ERP component interpreted in terms of distractor suppression (Wang et al 2019b), this has been taken as evidence that observers learn to down-modulate the attentional priority signals (Itti and Koch 2001;Fecteau and Munoz 2006;Wolfe and Gray 2007;Kok et al 2012;Aitken et al 2020) generated by distractors at frequent locations, thus reducing their potential to capture attention and cause interference. In line with this, we found that early visual-cortex signalling was reduced for distractors occurring in the frequent versus rare region.…”
Section: Discussionmentioning
confidence: 88%